Urban Youth Bulges and Social Disorder : An Empirical Study of Asian and Sub-Saharan African Cities - Urdal, Henrik (2012)
By 2050, two-thirds of the world s population will live in cities, and the greatest growth in urban populations will take place in the least developed countries. This presents many governments with considerable challenges related to urban governance and the provision of services and opportunities to a burgeoning urban population. Among the concerns is that large youth bulges in urban centers could be a source of political instability and violence. Here, we assess this claim empirically using newly collected data on city-level urban social disorder, ranging from non-violent actions, such as demonstrations and strikes, to violent political actions, such as riots, terrorism, and armed conflict. The dataset covers 55 major cities in Asia and Sub-Saharan Africa for 1960-2006. The study also utilizes a new United Nations Population Division dataset on urban populations by age and sex. The study further considers factors that could condition the effect of age structure, in particular the level of informal employment, economic growth, education, and gender imbalances. The analysis finds that large male youth bulges aged 15-24 are not generally associated with increased risks of either violent or non-violent social disturbance. Furthermore, the proxy measures of "youth exclusion" do not seem to increase the risk that large urban male youth bulges are associated with either form of disturbance. However, several other factors that may be associated with higher levels of youth exclusion - notably absence of democratic institutions, low economic growth, and low levels of secondary educational attainment - are significantly and robustly associated with increasing levels of urban social disturbance.